Visualizing influenza A virus assembly by in situ cryo-electron tomography - Wachsmuth-Melm, Moritz; Peterl, Sarah; O’Riain, Aidan; Makroczyova, Jana; Fischer, Konstantin; Krischuns, Tim; Vale-Costa, Sílvia; Amorim, Maria João; Chlanda, Petr (Nature Communications, 2025)
Influenza A virus (IAV) forms pleomorphic particles that package eight ribonucleoprotein complexes (vRNPs), each carrying a distinct RNA genome segment. vRNPs assemble in the nucleus and undergo selective sorting during Rab11a-mediated trafficking to the plasma membrane. Virion assembly is orchestrated by matrix protein 1 (M1), which forms a layer beneath the viral envelope containing hemagglutinin (HA) and neuraminidase (NA). However, molecular details of vRNP distribution, cytosolic trafficking, and coordination of IAV assembly remains unclear. Using in situ cryo-ET, we reveal that HA-containing membranes provide Rab11a-dependent platforms for membrane-assisted vRNP clustering, reducing inter-vRNP distances. In the absence of HA, vRNPs cluster on NA-containing membranes and virus assembly remains intact, indicating that vRNP clustering and trafficking is membrane-assisted but HA independent. The characteristic 7 + 1 vRNP bundle forms concomitantly with budding and is orchestrated by M1 layer assembly that precedes plasma membrane attachment. We further reveal that intracellular M1 forms multilayered helical assemblies of antiparallel dimers, structurally distinct from the M1 layer in virions. These assemblies are compact in the nucleus but partially dissociate in the cytoplasm, likely serving as a reservoir for budding. Together, our findings uncover membrane-assisted vRNP clustering and molecular details of M1 coordinated influenza virus assembly.